2019
DOI: 10.21815/jde.019.021
|View full text |Cite
|
Sign up to set email alerts
|

Admission Criteria as Predictors of Student Success in a Dental Hygiene Program

Abstract: The aims of this study were to assess which prerequisites the dental hygiene faculty at the University of Alberta perceived as essential to success in the dental hygiene program and to determine if students' prerequisite grades and interview scores predicted their success in the program. Academic records of students admitted between 2004 and 2013 were examined in 2016 for prerequisite course grades, interview scores, and junior, senior, and cumulative grade point average (GPA). In addition, course instructors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…These results are consistent with the findings from previous studies. 16,20,21,29 DISCUSSION a). R Squared = .768 (Adjusted R Squared = .402) b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with the findings from previous studies. 16,20,21,29 DISCUSSION a). R Squared = .768 (Adjusted R Squared = .402) b).…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15] Arguably, predictive admission procedures can reduce dropout rates, improve academic performance, increase success rates, and selectively exclude applicants who are unlikely to be successful in the course. [16][17][18] Furthermore, the aforementioned authors have unanimously indicated the value of predictive admission tests in providing rich information on the profile of students and informing curriculum design. The lack of these tests could therefore place students at risk of not completing their courses successfully.…”
mentioning
confidence: 99%
“…Additional research could explore whether prerequisite requirements offer a benefit or whether they could be eliminated 13 . Alternative admission approaches could be considered, such as competency‐based admission (CBA) models that are emerging in medical education.…”
Section: Discussionmentioning
confidence: 99%